Perbandingan Mata Pelajaran Sejarah Pada Kurikulum 2013 dan Kurikulum Merdeka - Armiyati, Laely; Djono, Djono (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
Kurikulum Merdeka is one of the government's efforts to realize Independent Learning policy (Merdeka Belajar), especially at the Primary and Middle School levels. This research aims to analyze the philosophical basis of the Kurikulum Merdeka as well as a comparison of History subjects in the 2013 Curriculum and the Merdeka Curriculum. The research method uses literature review with analytical techniques from Miles and Huberman, namely data collection, data reduction, data presentation, and drawing conclusions. The philosophical foundation of the Merdeka Curriculum comes from Ki Hadjar Dewantara's educational ideas and constructivism theory. Based on the comparison results, the similarities regarding the History subject in the Kurikulum Merdeka and the Kurikulum 2013 lie in the paradigm, namely using student-centered learning. In the Kurikulum Merdeka there are new terms in learning design, namely differentiated learning and teaching at the right level, but in essence these two terms are part of the student-centered learning paradigm. The differences between the Merdeka Curriculum and the 2013 Curriculum are in several aspects, namely planning, time allocation, subject objectives, internalized character values, learning design, scope of material, learning outcomes, assessment, and aspects of grade promotion.